Pengaruh Model Project Based Learning Berbasis Pembelajaran Diferensiasi Terhadap Creative Thinking Skill Dan Hasil Belajar Kognitif IPAS - Angel Dyah Pramesthi; Idam Ragil Widianto Atmojo; Roy Ardiansyah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2024)
Creative thinking skills are one of the skills that must be mastered in the 21st century. Increasing creative thinking skills can have an effect on increasing student learning outcomes. Implementation of a project based learning model based on differentiation learning can be used to develop creative thinking skills and student learning outcomes. This research was conducted to determine the effect of the project based learning model based on differentiation learning on the creative thinking skills and learning outcomes of class IV students at Gugus Srikandi Elementary School, Kaliwungu District in the 2023/2024 academic year. This research uses a quantitative approach with a non-equivalent quasi-experimental pre test-post test research design. The population of this study was all grade IV students at Gugus Srikandi Elementary School, Kaliwungu District in the 2023/2024 academic year using cluster random sampling techniques. This research uses multivariate analysis of variance to carry out data analysis tests. The research results are based on the MANOVA test with a significance value < 0.005 (0.000 < 0.005). These results show that there is a difference in the average creative thinking skill scores and student learning outcomes before and after using the project based learning model based on differentiation learning. Based on this, it can be concluded that the project based learning model based on differentiation learning has an influence on creative thinking skills and student learning outcomes.